Anti oxidant potential of Metformin and Pioglitazone in Type 2 Diabetes Mellitus: Beyond their anti glycemic effect. Issue 2 (April 2016) - Singh, R.K.; Gupta, B.; Tripathi, K.; Singh, S.K.
Abstract: Objective: Insulin sensitizers might influence oxidative stress to improve insulin resistance in diabetes mellitus. The present study was designed with the aim to study the effect of Metformin & Pioglitazone on markers of oxidative stress after 4 weeks of therapy in patients with type 2 diabetes mellitus (Type 2 DM). Research design and methods: This was a prospective study with follow up of 4 weeks in patients with Type 2 DM. They were randomized into metformin treated group ( N = 20) and Pioglitazone treated group ( N = 20) and healthy age-matched control group ( N = 20). Data was presented as mean ± S.D. Student " t " test, ANOVA and Pearson correlation co-efficient tests were performed to analyze the parametric data in this study. Results: Baseline clinical characteristics of the two study groups were similar. There is a significant difference for Fasting plasma glucose (FPG) and 2h-Post Prandial Plasma Glucose (PPPG) after 30 days of metformin and pioglitazone treatment. Metformin significantly reduced MDA ( p = 0.041) and increased SOD ( p < 0.001). Pioglitazone significantly reduced MDA ( p < 0.001) but failed to raise SOD level ( p = 0.132). Mean MDA was 4.57 ± 0.57 μM/L in metformin and 2.91 ± 0.66 μM/L in pioglitazone treatment with a p-value of <0.001. Further, a similar significant difference was obtained for SOD value by metformin and pioglitazone treatment (7.87 ± 0.72 U/ml vs. 6.94 ± 0.53 U/ml; p < 0.001). Conclusion: Pioglitazone was superior to Metformin to improve oxidative stress as reflected by reduction in MDA but the antioxidant effect i.e. increase in SOD was seen with metformin only. The differing mechanism of actions of the two drugs on oxidative stress favors co prescription of these drugs for better outcome in improving insulin resistance and diabetic complications.